2019
DOI: 10.1039/c9em00283a
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for finding Junge variability-lifetime relationships for micropollutants in the Danube river

Abstract: Junge variability-lifetime relationships could potentially be used to infer persistence of micropollutants in rivers from field measurements of concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(61 reference statements)
0
1
1
Order By: Relevance
“…While furosemide was previously considered recalcitrant to biodegradation, biotransformation in sediments has been reported recently [41], and the current study suggests the organic carbon content may influence such biotransformation. Though the majority of previous studies reported carbamazepine as relatively persistent to biodegradation [4,16,34,42,43], up to 60% removal of carbamazepine in a mixed bacterial culture has been reported [44]. In the current study, removal in the biotic microcosms was only marginally higher than in the abiotic setup suggesting possible contribution of both mechanisms in its removal as carbamazepine sorbs readily to organic matter in sediment-water systems due to its relatively high log D ow of 2.8 [24].…”
Section: Influence Of Toc On Biotransformation and Sorption Of Trocscontrasting
confidence: 53%
“…While furosemide was previously considered recalcitrant to biodegradation, biotransformation in sediments has been reported recently [41], and the current study suggests the organic carbon content may influence such biotransformation. Though the majority of previous studies reported carbamazepine as relatively persistent to biodegradation [4,16,34,42,43], up to 60% removal of carbamazepine in a mixed bacterial culture has been reported [44]. In the current study, removal in the biotic microcosms was only marginally higher than in the abiotic setup suggesting possible contribution of both mechanisms in its removal as carbamazepine sorbs readily to organic matter in sediment-water systems due to its relatively high log D ow of 2.8 [24].…”
Section: Influence Of Toc On Biotransformation and Sorption Of Trocscontrasting
confidence: 53%
“…In situ monitoring data and characterization of partitioning and degradation rates are not available for the great majority of case studies. The degradation rates, in particular, are obtained from laboratory experiments or in silico (as a function of structure); the extrapolation to river conditions carries large uncertainties [240]. Recent modelling of TrOC in the Rhine River basin showed that degradation rates in small-and medium-sized streams, where the HZ is usually most important, are being underestimated [237].…”
Section: Innovative Modelling Approachesmentioning
confidence: 99%